Relevance of HLA-DP/DQ and ICAM-1 SNPs among Ovarian Cancer Patients - Ghazy, Amany A.; El-Etreby, Nour M. (Frontiers in Immunology, 2016)
Background Ovarian cancer is one of the most lethal gynecological malignancies and the fifth leading cause of cancer deaths among women. The high mortality rate is largely attributed to its diagnosis in advanced stages. Poor prognosis of ovarian cancer is usually due to the lack of specific or effective screening and diagnostic methods for identifying early-stage disease. Aim Our study aimed to study the role of HLA-DP, HLA-DQ, and ICAM-1 SNPs in diagnosis and/or prognosis of ovarian tumors Subjects and methods The current study was conducted on 60 patients with ovarian tumors (benign, borderline, and malignant) and 20 healthy volunteers. Genotyping of HLA-DP rs3077, HLA-DQ rs3920, and ICAM-1 rs1437 SNPs was done using 5′ nuclease assay. Results We found significant association of HLA-DP rs3077 AA, HLA-DQ rs3920 GG, ICAM-1 rs1437 CC, and CT genotypes with increased risk of ovarian cancer (OR = 43.5, 6, 25, and 2.6, respectively). In addition, HLA-DQ rs3920 and ICAM-1 rs1437 alleles vary significantly among different types of ovarian cancer (P = 0.003 and 0.001, respectively). Conclusion HLA-DP rs3077, HLA-DQ rs3920, and ICAM-1 rs1437 SNPs could help in the diagnosis and prognosis of ovarian cancer.